Control Method of Roadway Surrounding Rock Under the Influence of Residual Coal Pillars in Goaf - Huang, Dongshan (International Journal of Natural Resources and Environmental Studies, 2024)
In the process of close coal seam mining, the lower coal seam is affected by the concentrated stress of the remaining coal pillars in the goaf area of the upper coal seam, and the surrounding rock of the roadway may appear in the surrounding rock of the roadway, such as large deformation, strong sheet gang, and roofing, and the targeted surrounding rock control countermeasures are the key to ensure the stability of the surrounding rock. In order to solve the above problems, taking the thick-topped coal mining roadway of the B1 coal seam of Kuangou mine as the engineering background, the comprehensive research methods such as numerical simulation, theoretical analysis and field test were used to analyze the environmental characteristics of high deviator stress, such as the maximum principal stress and the difference of principal stress at different roadway locations of the B1 coal seam under the influence of the legacy coal pillars, and the plastic failure law of the surrounding rock under the action. The results show that under the condition of the remaining coal pillars in the 15m goaf, the maximum principal stress concentration area is located in the range of 10.0m 15.0m, and the peak value is about 0.95 times of the original rock stress.